Climate Reparations as Ecological Debt: A Challenge to Distributive Justice Frameworks - DAVID, Vareba Dinebari (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
The prevailing ethical frameworks for addressing climate change, predominantly rooted in distributive justice, focus on the fair allocation of burdens and benefits for mitigation and adaptation. Principles like “polluter pays” and “ability to pay” guide contemporary climate finance. However, this paper argues that distributive justice models are insufficient because they often fail to adequately account for the historical dimension of climate change, thereby treating it as a contemporary problem of allocation rather than a legacy of historical injustice. This paper proposes the framework of “climate reparations” grounded in the concept of “ecological debt” as a necessary and more robust alternative. It contends that climate finance must be understood not merely as aid or distribution, but as restitution for a debt accrued by industrialized nations through their historical and disproportionate appropriation of the atmospheric commons. The paper will critically analyze the limitations of distributive justice, elucidate the philosophical and economic foundations of ecological debt, and defend the reparations model against charges of being impractical or historically convoluted. Through case studies of demands from the Alliance of Small Island States (AOSIS) and the discourse around “Loss and Damage,” it will demonstrate that the reparative justice framework offers a more morally coherent and politically salient approach, aligning climate action with demands for historical accountability and corrective justice.